2012
DOI: 10.1002/jor.22186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sclerostin antibody on healing of a non‐critical size femoral bone defect

Abstract: Sclerostin is a glycoprotein secreted by osteocytes and inhibits osteoblastogenesis via inhibition of Wnt signaling. We hypothesized that sclerostin antibody (Scl-AbIII) would accelerate the healing of a murine femoral non-critical size bone defect model. A unilateral and unicortical 0.8 mm-sized drill hole was made in the proximal femoral shaft of adult female nude mice. One group of mice received subcutaneous injections of Scl-AbIII and a second group received vehicle only. Reporter MC3T3 osteoprogenitor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 32 publications
(54 reference statements)
0
24
0
Order By: Relevance
“…Sclerostin negatively regulates bone formation, and the development of Sclerostin inhibitory strategies provides a potential opportunity to enhance bone repair. Deficiency or antagonism of Sclerostin improves intramembranous ossification [22,[24][25][26][27][28][29]38], though the effect on endochondral ossification during fracture repair is not as well defined. We hypothesized that endochondral repair would be improved within the Sost −/− mouse in comparison to C57Bl/ 6J wild type controls, with earlier bony union, and resultant denser and stronger mineralized calluses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Sclerostin negatively regulates bone formation, and the development of Sclerostin inhibitory strategies provides a potential opportunity to enhance bone repair. Deficiency or antagonism of Sclerostin improves intramembranous ossification [22,[24][25][26][27][28][29]38], though the effect on endochondral ossification during fracture repair is not as well defined. We hypothesized that endochondral repair would be improved within the Sost −/− mouse in comparison to C57Bl/ 6J wild type controls, with earlier bony union, and resultant denser and stronger mineralized calluses.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, the development and subsequent animal and human trials of anti-Sclerostin antibodies have provided evidence of stimulated bone formation and enhanced bone mass [17][18][19][20][21][22][23]. The anabolic effects of Sclerostin deficiency, via genetic knockout mice or anti-Sclerostin antibody treatment, have also been demonstrated in intramembranous bone healing studies [24][25][26][27][28][29]. These anabolic effects include increases in bone mineral density, bone volume and mechanical strength.…”
Section: Introductionmentioning
confidence: 93%
“…At six weeks, the maximum failure load was increased by 68% 70 . Sclerostin antibody administered to rats with a critical-sized femoral defect and mice with a non-criticalsized femoral defect showed earlier healing, complete union, and physiologic maturation of the defect 71,72 . Similar conclusions can be drawn from the rat model of experimental periodontitis, in which sclerostin antibody treatment increased alveolar bone regeneration and filled substantial oral bone defects 73 .…”
mentioning
confidence: 98%
“…At later time points, this leads to higher mineral content in the abundantly formed new bone, thereby potentially increasing mechanical stability. Furthermore, early reports that successfully used Sost antibody treatment to promote fracture healing relied heavily on models that primarily healed by intramembranous bone formation [94,140,152,153]. This suggested that SostAb may be beneficial in problematic fracture healing that results from poor osteogenesis; however, Li et al (2011) [154] reported fracture repair in an endochondral model in Sost -/-mice, and Feng et al (2015) [155] reported similar results with Sost antibody treatment, suggesting that fracture repair may benefit from early intervention by reducing sclerostin levels, rather than only during osteogenesis.…”
Section: Discussionmentioning
confidence: 99%